Pengaruh Slack Resources, Dewan Direksi, dan Komite CSR terhadap Sustainability Report - Siti Zhaviratul Hanan; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine the effect of slack resources, the board of directors, and the CSR committee on the sustainability report. The population in this study are several mining and agricultural companies listed on the Indonesia Stock Exchange from 2017-2021. This study uses secondary data. The sampling technique used purposive sampling method with a sample of 26 companies over a period of 5 years. Use logistic regression analysis as a data analysis technique in this study. The results of the study show that slack resources and the board of directors have no effect on the sustainability report. Meanwhile, the CSR committee has an effect on the sustainability report. The next researcher can consider using other variables such as public share ownership, CEO duality, and other variables that might influence sustainability report.